A new inhomogeneous partially reflecting surface for Fabry‐Perot antenna to reduce side lobe level. Issue 7 (25th March 2020) - Zaiter, Sabrina; Raveu, Nathalie; Oussaid, Rachid
Abstract: In this article, an extension of the spatial filter method to study Fabry‐Perot antennas with homogeneous or inhomogeneous partially reflecting surface (PRS) of finite size is proposed. This tool was subsequently validated through the study of different Fabry‐Perot antennas, with homogeneous PRS and inhomogeneous GRadient‐INdex (GRIN) PRS that present very high side lobe level (SLL). Since they are due to structure truncation, a new inhomogeneous PRS to reduce the SLL is designed with the new analytical tool. The new inhomogeneous PRS for Fabry‐Perot antenna is characterized by simulations and measurements. Compared to the homogeneous PRS antenna, the proposed PRS allows a SLL reduction of 5 dB without decreasing the 14 dBi directivity.